MELACAK OTENTISITAS HUKUM ISLAM DALAM HADIS NABI (STUDI PEMIKIRAN JOSEPHT SCHACHT) - moh, muhtador (Istinbath : Jurnal Hukum, 2017)
This paper attempts to explore the subject matter of figures associated with Islamic law orientalis. A study of Islamic law that continues to grow along with the development problems of humanity will experience significant changes. But in a different region, examines Islamic law to track the history through religious teachings is also important, as the work done Joseph Schacht. Schacht paradigm in studying Islamic law is different from other Muslim kesarjaan, skepticism and criticism of history into a blade analysis in studying Islamic law. So that the conclusions obtained in contrast to the majority of other thinkers. Schacht doubted the authenticity of Islamic law as a product of the doctrine, the article of the development of Islamic law can not be separated from the interests of the authorities. Tulisan ini mencoba untuk menelusuri ulang pokok pikiran dari tokoh orientalis terkait dengan hukum Islam. Kajian yang hukum Islam yang terus berkembang bersamaan dengan perkembangan problem kemanusiaan akan mengalami perubahan-perubahan secara signifikan. Namun pada wilayah berbeda, mengkaji hukum Islam dengan melacak sejarah melalui ajaran agama juga tidak kalah penting, seperti usaha yang dilakukan Joseph Schacht. Paradgima Schacht dalam mengkaji hukum Islam berbeda dengan kesarjaan muslim lainnya, skeptisme dan kritiik sejarah menjadi pisau analisi dalam mengkaji hukum Islam. Sehingga kesimpulan yang didapat berbeda dengan mayoritas pemikir lainnya. Schacht meragukan otentisitas hukum Islam sebagai produk ajaran, pasalnya perkembangan hukum Islam tidak lepas dari kepentingan otoritas.